Herpes Zoster as the Presenting Manifestation of Systemic Lupus Erythematosus (SLE): A Rare Case Report - Qureshi, Arshna (J Clin Diagn Res, 2016)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease and is usually diagnosed with the SLICC criteria. Here we report a case of SLE presenting as Herpes Zoster (HZ). She had presented with painful vesicular eruptions from 8(th) thoracic nerve to 10(th) thoracic nerve segments and oliguria. There were no clinical manifestations suggestive of SLE. However, on further workup, haematological and immunologic laboratory profiles were suggestive of SLE. A diagnosis of lupus nephropathy was confirmed by renal biopsy and final diagnosis of SLE as the underlying systemic illness associated with HZ was established. We report this case because this patient had none of the manifestations of SLE, as a result of which this would have been an incomplete diagnosis.